2018
DOI: 10.1016/j.dib.2017.11.099
|View full text |Cite
|
Sign up to set email alerts
|

Data on corrosion and scaling potential of drinking water resources using stability indices in Jolfa, East Azerbaijan, Iran

Abstract: This cross-sectional study was conducted on the drinking water resources of the city of Jolfa (East Azerbaijan province, Iran) from samples taken from 30 wells. Calcium hardness, pH, total alkalinity, TDS, temperature and other chemical parameters were measured using standard methods. The Langelier, Rayzner, Puckhorius and aggressive indices were calculated. The results showed that the Langelier, Reynar, Puckorius, Larson-skold and aggressive indices were 1.15 (± 0.43), 6.92 (± 0.54), 6.42 (± 0.9), 0.85 (± 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Yousefi et al studied drinking water of Jolfa, reported LSI, RSI, PSI and AI respectively as 1.15 (± 0.43), 6.92 (± 0.54), 6.42 (± 0.9), and 12.79 (+ 0.47). Data revealed that the well water in this study was corrosive (23). In the Arko study on the scale formation capacity of underground water in a district in Turkey (related to 12 wells), results showed that water was not corrosive, with one exception due to high sulfate concentrations.…”
Section: According Tomentioning
confidence: 51%
See 1 more Smart Citation
“…Yousefi et al studied drinking water of Jolfa, reported LSI, RSI, PSI and AI respectively as 1.15 (± 0.43), 6.92 (± 0.54), 6.42 (± 0.9), and 12.79 (+ 0.47). Data revealed that the well water in this study was corrosive (23). In the Arko study on the scale formation capacity of underground water in a district in Turkey (related to 12 wells), results showed that water was not corrosive, with one exception due to high sulfate concentrations.…”
Section: According Tomentioning
confidence: 51%
“…In this process, double-capacity cations such as calcium and magnesium react with other dissolved materials in water to form layers of scales on the inner walls of pipes. One such common layer is calcium carbonate which is considered an indicator in determining scale formation (7,8). Potable water and other types of usable water in industry and agribusiness should be non-corrosive in order to be considered appropriate by valid universal standards.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the microbial quality of drinking water in villages of Zahedan city, 168 villages were selected as a comprehensive sample of all villages in this city. Between 2014–2015, 1221 microbial samples were prepared from the water facilities installed in these villages, and the microbial test was performed by MPN, P-A or MF methods and turbidity, temperature, and HPC tests based on the standard method [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Microbial parameters measurements, including the most probable number of coliforms (MPN) and fecal coliforms by multi-pipe fermentation method [1], [2], [3], [4], [5], [6], [7], [8], [9], [10].Data formatRaw, analyzedExperimental factorsThe mentioned parameters above, in abstract section, were analyzed according to the standards for water and wastewater treatment handbook.Experimental featuresVery brief experimental descriptionData source locationTorbat-e Heydarieh, Khorasan-e-Razavi province, IranData accessibilityThe data are available with this article…”
mentioning
confidence: 99%